1988
DOI: 10.1182/blood.v71.1.263.263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGF-beta gene in adult T cell leukemia

Abstract: Peripheral mononuclear cells from adult T cell leukemia (ATL) patients were analyzed in comparison with other types of leukemia cells, for the expression of transforming growth factor-beta (TGF-beta) mRNA, for the presence of TGF-beta activity (colony stimulating activity for normal rat kidney fibroblasts [NRK]) in conditioned medium and for their susceptibility to exogenous TGF-beta. Highly elevated TGF-beta mRNA levels were observed in all five ATL cell samples tested; however, in three acute myelogenous leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Their interactions and functions within the pathway are essential for proper cellular responses to TGF-β signaling [ 37 , 38 , 39 ]. Several studies have shown that abnormal expression of miRNAs can affect TGF-β signaling [ 40 ], which plays a critical role in ATLL development and progression [ 41 , 42 ]. For example, miR-26b was shown to downregulate the expression of SMAD-4, a negative regulator of TGF-β signaling, thereby promoting TGF-β signaling in affected cells [ 43 ] including leukemic cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their interactions and functions within the pathway are essential for proper cellular responses to TGF-β signaling [ 37 , 38 , 39 ]. Several studies have shown that abnormal expression of miRNAs can affect TGF-β signaling [ 40 ], which plays a critical role in ATLL development and progression [ 41 , 42 ]. For example, miR-26b was shown to downregulate the expression of SMAD-4, a negative regulator of TGF-β signaling, thereby promoting TGF-β signaling in affected cells [ 43 ] including leukemic cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decontrolled immune response for the most part by means of tolerogenic state enlistment has been recorded as an additional factor (Kannagi et al, 2012). A tolerogenic state is accomplished through the direct impact of Interleukin-10 (Mori et al, 1996) and Transforming growth factor-beta (TGFβ) (Niitsu et al, 1988) generated by infected cells. It is also achieved through the indirect activity of C-C theme chemokine ligand 22 (CCL22) produced by cells having an infection of HTLV-1 (Toulza et al, 2010).…”
Section: Phenotypic Markersmentioning
confidence: 99%